Pertentangan keluarga dalam novel terpilih Fatimah Busu - M. Zubir Siti Khariah, Ismail Nor Hasimah, (N/A, 2014)
Pertentangan keluarga dalam novel terpilih Fatimah Busu by M. Zubir Siti Khariah, Ismail Nor Hasimah,